Developing English Speaking Skills by Using Voice Note Friend to Motivate Silent Students at MA Mambaul Jenggawah - Jannah, Nur Intan Roudhatul; Wardani, Ika Desy (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
This thinks about points to create students' English talking aptitudes at MA Mambaul Ulum Jenggawah by utilizing the "Voice Note Friend" strategy to persuade understudies who tend to be calm. Within the setting of English learning, understudies who are not effectively talking regularly have trouble communicating and taking an interest in the course. This consider applies the voice notes technique, which could be a voice message sent by a classmate, as an apparatus to extend students' inspiration and certainty in practicing speaking English. Through this approach, understudies are anticipated to feel more comfortable and energized to talk, which in turn will make strides in their talking aptitudes. This considers employment the subjective Classroom activity research method to degree the viability of this approach, with comes about appearing a noteworthy increment within the interest and talking abilities of understudies who already tended to be calm.